Kajian Kelayakan Teknis Dan Ekonomis Pemindahan Kapal Boeing Jetfoil Nyi Ageng Serang - Hardjono, Soegeng (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
BPPT's Boeing Jet.foil ziessel of Nyi Ageng Sernng (BJ-NAS) /ms recently been lmjng dawn in a riverbank of Indonesian Nmry territon1 in Belmmn, Medizn and not yet been in operation anynwre due toboth engine failure and hull leakage. 11re ziessel condition itself /ms been getting worse since the repairprocess has been facing difficulties in getting engine's spare parts. To cape with this problem, it hasbeen proposed 3 (Three) transfer technique alternatives to bring this vessel back to her home base inPT. PAL Surabm1a. 11wse alternatives are firstly, the ziessel would be laid doz1m on the barge and thenpulled btj tugboat, secondly, the ziessel would be mrried btJ LCT vessel and thirdl.y, the z ssel wouldbe tied up in the port side of tugboat along the wm1 to Surabm;a. Hm1ing analysed tlwse 3 (three)alternatives both technical and economicnl feasibilities from uiewpoint of infrastructures, facilities,human resource, time, safety, cost and admntngeous criteria, it appears that the third alternativeseems to be the best to be implemented. Howeuer, wmie condition slwuld be taken into Eeriouslyconsideration when dealing with the safety of ship. 771f expected mlm water for ship unden.11m1 toSurabm1a is in betz1 April and June.Keywords : Boeing Jet.foil vessel, Transfer technique alternatives, Tedino Economic FeasibilihJ